Comparative Study of Teacher Concepts from the Perspective of Ibn Khaldun an Al-Ghazali and Their Relevance to Teacher Competence - Muhammad Romli; Muhammad Ufuqul Mubin (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2023)
This study was designed using the type of research library research (library research). And the data collection method used is the documentation method. The primary data sources are the books of Ibn Khaldun, al-Ghazali, and the Permendiknas Book Number 16 of 2007. While the secondary sources are: other supporting books related to the concept of the teacher. Meanwhile, in analyzing the data the author uses content analysis techniques. The results of this study indicate that the concept of teacher perspective of Ibn Khaldun and al-Ghazali which is relevant to Permendiknas Number 16 of 2007 is that the teacher must; a) gentle and loving to students b) Mastering the material and having scientific specialization c) Teachers must always improve their quality d) Prioritizing moral education and character of children e) Sincere in teaching f) Teaching directly face to face g) Providing lessons according to ability students and not overdo it h) Mastering learning methods i) Respectful and authoritative j) Giving advice to students gently k) having noble character and can be an example for students